Nutritional parameters of sheep fed diets based on grass silage with brewery residue and a concentrate with rice bran - Anderson de Moura Zanine; Breno de Moura Gimenez; Daniele de Jesus Ferreira; Michelle de Oliveira Maia Parente; Henrique Nunes Parente; Edson Mauro Santos; Glayciane Costa Gois; Fleming Sena Campos; Luana Milena Pinheiro Rodrigues; Jessica Maria de Sousa Oliveira; Nelquides Braz Viana; Daimy Salas Aguilar; et al. (AIMS Agriculture and Food)
The objective was to evaluate the intake, digestibility, and feeding behavior of sheep receiving diets based on marandu grass silage (MGS) with different levels of dehydrated brewery residue (DBR) inclusion and different types of concentrates. Sixteen sheep (30 ± 1.46 kg and 12 months old) were distributed in a randomized block experimental design. The treatments were: MGS containing 10% DBR + concentrate (100% corn); MGS containing 10% DBR + concentrate (50% corn and 50% rice bran); MGS containing 30% DBR + concentrate (100% corn); MGS containing 30% DBR + concentrate (50% corn and 50% rice bran), with 4 replicates per treatment. The experimental period lasted 21 days. Regardless of the concentrate used, diets containing MGS + 30% DBR provided the animals with higher intakes and digestibility of dry matter (DM) and nutrients, water intake, and urinary pH (p < 0.05). Longer feeding and rumination times and periods, and shorter idle times, feeding efficiency of DM, feeding and rumination efficiency of neutral detergent fiber (NDF), and intakes of DM and NDF per meal were shown by sheep-fed diets containing MGS + 10% DBR (p < 0.05). The use of 100% corn concentrate also resulted in lower rumination efficiency of NDF and a higher number of mericic chews associated with MGS + 10% DBR (p < 0.05). Diets containing MGS + 30% DBR and concentrate (50% corn + 50% rice bran) resulted in shorter rumination and total chewing times (in min/kg/NDF) (p < 0.05). The use of MGS ensiled with 30% BR in sheep diets improves dry matter intake and nutrient digestibility.